Quand l’État devient banquier - Isabelle Chambost; Béatrice Touchelay (Revue de la Régulation)
This article analyses the structures put in place by the State at the Liberation to manage its holdings in the four nationalized deposit banks. Pointing out the discrepancies between its stated intentions, particularly its capacity to manage productively, and its achievements, this article highlights the difficulties encountered in implementing this control. These tensions, linked to the diversity of bankers’ interests and the very high tensions at the top of the state, appear as soon as one crosses the scales of analysis, the macro scale - of the law and its national application - and the micro scale, of a bank (the Société Générale) that has become part of the bosom of the state. To understand some of the reasons behind these reforms, we have placed them in a historical perspective, pointing out the continuities and ruptures. It shows that the State as shareholder is rooted in the imperfections of the previous system, that of the "erased State", from the beginning of the 20th century to the outbreak of the Second World War, and then in an asserted political will to install a "partner State" from 1940 to 1945 where the State entered, not without difficulty until the sixties, alongside the banking corporation.